Role of public entities in suitable provision of public services: Case study from Slovakia - Viera Papcunová; Roman Vavrek; Marek Dvořák (Administrative Sciences, 2021)
Local governments in the Slovak Republic are important in public administration and form an important part of the public sector, as they provide various public services. Until 1990, all public services were provided only by the state. The reform of public administration began in 1990 with the decentralization of competencies. Several competencies were transferred to local governments from the state, and thus municipalities began to provide public services that the state previously provided. Registry offices were the first to be acquired by local governments from the state. This study aimed to characterize the transfer of competencies and their financing from state administration to local government using the example of registry offices in the Slovak Republic. In the paper, we evaluated the financing of this competency from 2007 to 2018 at the level of individual regions of the Slovak Republic. The results of the analysis and testing of hypotheses indicated that a higher number of inhabitants in individual regions did not affect the number of actions at these offices, despite the fact that the main role of the registry office is to keep registry books, in which events, such as births, weddings, and deaths, are registered.
Keywords: 350; public sector; local government; registry office; suitable management; transferred competencies